UPAYA HUKUM DALAM MEMINIMALISIR ILLEGAL FISHING TERKAIT KAWASAN ZEE (ZONA EKONOMI EKSKLUSIF) INDONESIA - Humaira Afdini; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
Indonesia is a maritime country and has many marine resources in it. The wealth of marine resources owned by Indonesian waters is also related to the ZEEI area, which invites rampant cases of illegal fishing. There are many impacts of this rampant illegal fishing. Illegal fishing has an impact on the fisheries sector and the Indonesian economy. as well as the destruction of marine resource ecosystems and other marine biota. The scarcity of marine life in the ZEEI area is the origin of the abundant number of cases in the ZEEI area. Therefore, strong legal efforts are needed to overcome illegal fishing and government efforts to prevent illegal fishing. legal efforts taken by the government are to ratify laws regarding regulations in the EEZ area. Moreover, such as making regulations for the minister of marine and fisheries and in preventing illegal fishing the government makes efforts by increasing the task force in the ZEEI area. and besides by using advanced technology to detect the activities of other ships and so on. Based on this paper, it is necessary to increase the government's endeavor in bridling the problem of illegal fishing and a firm attitude is needed from law enforcers in the territorial waters to confer an obviation repercussion to the evil-doers of illegal fishing